SYNTHESIS OF POLYANILINE MICROCELLULOSE COMPOSITE - Lela Mukmilah Yuningsih; Dikdik Mulyadi; Devia Indriani (Jurnal Kimia dan Kemasan, 2021)
In this study, the Polyaniline-Microcellulose composite was produced as a solid electrolyte. In the previous research, polyaniline-cellulose composite has been carried out. However, the electronegativity and electrical voltage are still below the conventional batteries. In order to increase its performance, a polyaniline-microcellulose composite was synthesized. The purpose of this research is to determine the effect of the Polyaniline-Microcellulose composite on its conductivity and voltage values. Microcellulose synthesis used a combination method of sulfuric acid hydrolysis with concentrations of  30%-64% and sonication. Polyaniline - Microcellulose composite was synthesized via polymerization of aniline using chemical oxidation and sonication. Microcellulose was characterized using particle size analyzer (PSA). Microcellulose and PANI-microcellulose composites were characterized using FTIR, SEM-EDX, and XRD. The conductivity values and electrical quantities of PANI-Microcellulose composite were measured using LCR-meter and Digital Multimeter, respectively. The diameter of the microcellulose particles were between 20 nm – 40,6 µm. Microcellulose and PANI-Microcellulose composites showed identical absorption bands, namely the stretching vibrations to-OH and CH (aliphatic), which were shown at wavelengths 3444.87 cm-1 and 2897.08 cm-1, two typical groups of cellulose. The typical groups of PANI are bending vibrations from N-H, stretching vibrations of C=C, C-N, and quinoid ring C=N at wavelengths 1566.20 cm-1, 1479.40 cm-1, 1300.02 cm-1, and 1141.86 cm-1. PANI-Microcellulose composite morphology showed that PANI had been dispersed on microcellulose and free from impurities. The degrees of crystallinity are 30.9343% for microcellulose and 14.6079% for PANI-microcellulose. The optimum conductivity value of PANI-microcellulose composite at a ratio of 1:10 is 0.036013 S/cm; the electrical voltage is 1.34 volts with an electric current of 83 mA.